A menthol-enhanced "cooling" energy gel does not influence laboratory time trial performance in trained runners - Vogel, R. M.; Varone, N.; Clark, C.; Ramirez, K.; Ross, M. L. R.; Swann, C.; Stevens, C. J. (Nutrients, 2023)
l-menthol (menthol) is an organic compound derived from peppermint which imparts a refreshing mint flavor and aroma to oral hygiene products, chewing gum, and topical analgesics. Menthol has been identified as a non-thermal sensory cooling strategy for athletes when ingested or mouth-rinsed during exercise in hot environments. Therefore, sports nutrition products delivering a controlled concentration of menthol could be beneficial for athletes exercising in the heat. We sought to test the performance and perceptual outcomes of a novel menthol energy gel during treadmill running in the heat (33 °C, 49% RH). Fourteen trained runners (mean ± SD; age: 31 ± 6 years, VO2max: 56.5 ± 10.1 mL·kg-1·min-1, BMI: 23.2 ± 2.4 kg/m2; six female) participated in a randomized, crossover, double-blind, and placebo-controlled study. A menthol-enhanced energy gel (0.5% concentration; MEN) or flavor-matched placebo (PLA) was ingested 5 min before and again at 20 and 40 min of a 40 min treadmill exercise preload at 60% VO2max, followed by a 20 min self-paced time trial. The total distance, vertical distance, perceptual measures (thermal comfort, thermal sensation, rating of perceived exertion, and affect), and cognitive performance via computerized neurocognitive assessment were measured. No difference between 20 min self-paced time trial total distance (MEN: 4.22 ± 0.54 km, PLA: 4.22 ± 0.55 km, p = 0.867), vertical distance (MEN: 49.2 ± 24.6 m, PLA: 44.4 ± 11.4 m, p = 0.516), or any perceptual measures was observed (all p > 0.05). Cognitive performance was not different between the trials (all p > 0.05). These results suggest that a menthol energy gel is not superior to a non-menthol gel in terms of performance or perception during treadmill running in the heat. More research is needed to confirm whether these findings translate to ecologically valid settings, including outdoor exercise in ambient heat and during competition.